Analysis of Online Gambling Behavior Among College Students in Makassar City - Muh Rijal; Ibrahim Arifin; A. Noer Chalifa Ramadhany; Indriani Indriani; Irwan Nur (Indonesian Journal Publisher, 2026)
Online gambling remains a serious problem among college students. Students who should be focused on learning and developing academic competencies are potentially distracted by addictive online gambling activities. This study aims to identify the factors that drive students to engage in online gambling and the impacts of online gambling. The method used was a descriptive qualitative approach with a purposive sampling technique involving 10 student informants from various campuses in Makassar City. The results showed that factors that drive students to engage in online gambling include: a) peer factors, b) social media exposure, and c) economic factors. The impacts of online gambling experienced by students include: a) stress and anxiety, b) repeated losses, and c) decreased academic performance. Therefore, students need to be provided with an understanding and education regarding the dangers of online gambling on their financial, psychological, and academic conditions. Digital literacy and financial literacy education are important steps to help students understand that gambling is not an economic solution, but rather a high-risk activity that can lead to repeated losses and addiction.